Diversidad genética de Handroanthus heptaphyllus a partir de calidad fisiológica de semillas - Valdovinos, Tamara Mariel [UNESP]; de Paula, Rinaldo Cesar [UNESP] (Sistema de Bibliotecas UACH, 2017)
Handroanthus heptaphyllus (lapacho negro) is one species that stands out for its high economic value, mainly for the high quality of its wood; it is also required for medicinal use, landscaping and urban forestry projects. This study aimed at determining the genetic diversity among H. heptaphyllus mother trees from traits of seed physiological quality, evaluated in tests of germination and vigor; and to identify the most influential variables for genetic diversity among trees. The seeds were collected from 25 mother trees, located in the city of Jaboticabal, Sao Paulo, Brazil. In total, 11 traits of physiological quality of seeds, determined by germination, electrical conductivity, accelerated aging and submersion tests, were evaluated. Five replications of 20 seeds were used for each mother tree evaluated. Genetic diversity was assessed using the hierarchical method of Ward and dispersion by Principal Components from the Euclidean Distance calculated between pairs of access. Genetic diversity among the mother trees was expressive. The peak value and electric conductivity were the most effective traits for differentiating trees. The distribution of 25 mother trees in the bi-dimensional plane, from the analysis of the main components, detected the similarities and differences among the trees, based on the evaluated traits, and was consistent with the clusters formed with the Ward’s method. The peak value, synchronization index and seedlings length were the variables with higher diversity. This result allows the identification of mother trees for seed collection, supporting conservation programs and genetic improvement of this species.
Genetic diversity of handroanthus heptaphyllus from seed physiological quality
Keywords: Breeding; Clusters analysis; Conservation; Germination and vigor